Serene manta armchair / Nur Zulaikha Mohd Zahiruddin - Mohd Zahiruddin, Nur Zulaikha (Universiti Teknologi MARA, Kedah, 2024)
Imagine an armchair that embodies the graceful glide of a manta ray. The Manta Ray Armchair, Serene Manta, captures the essence of this majestic creature through its design. It captures the essence of this majestic creature with its flowing curves and luxurious comfort. Inspired by the manta ray's wide, diamond-shaped body, the armchair features a gently sloping backrest that extends outwards to form wide armrests. Velvety materials provide a sense of comfort and serenity. This armchair is a perfect blend of art and functionality, offering a unique seating experience that is both stylish and relaxing. Upholstered in soft, textured fabrics that resemble the manta ray's smooth skin, the armchair invites you to sink in and unwind. The use of contrasting colors can further highlight the design's biomimicry. The Manta Ray Armchair is not just a piece of furniture, it's a sculptural statement that brings the beauty of the ocean into your living space. Its unique form is sure to spark conversation and inspire awe, while its exceptional comfort beckons you to relax and recharge.